Laparoscopic surgery for colorectal cancer in patients over 80 years of age: the morbidity outcomes - Lim, Sang Woo (Ann Surg Treat Res, 2017)
PURPOSE: The aim of this study was to compare the outcomes between patients under 60 years of age and older patients over 80 years of age who underwent laparoscopic colorectal surgery with colorectal cancer. METHODS: A retrospective analysis of 519 colorectal patients who underwent laparoscopic colorectal surgery for colorectal adenocarcinoma between January 2007 and December 2012 was collected and categorized into 2 groups of patients, those under 60 years of age (n = 404) and those over 80 years of age (n = 115). RESULTS: The group of patients over 80 years of age had a significantly higher ASA physical status classification (P < 0.001), more preoperative comorbidities (P < 0.001), had a tendency towards more tumors in a colonic location (P = 0.034), and more advanced American Joint Committee on Cancer TNM stage (P = 0.001). A higher proportion of right hemicolectomy and abdominoperineal resection was performed and more transfusions were required in the group of patients over 80 years of age (P = 0.002 and P = 0.001, respectively). There were no significant differences in operative time, conversion rate, resection margins, and numbers of harvested lymph nodes, hospital stay, and morbidity between the 2 groups. No postoperative mortality was found in the present study. The 3-year DFS for over 80 years age group and under 60 years age group were 73.5% and 73.9%, respectively (P = 0.770). CONCLUSION: Laparoscopic colorectal surgery was effective and safe for elderly patients over 80 years of age and resulted in postoperative outcomes similar to those in younger patients. The postoperative morbidity after laparoscopic colorectal cancer surgery was not increased in over 80 years of age.